2019
DOI: 10.1111/iju.14091
|View full text |Cite
|
Sign up to set email alerts
|

Single use versus reusable digital flexible ureteroscopes: A prospective comparative study

Abstract: Objectives To compare the performance and surgical outcomes of two different single‐use digital flexible ureteroscopes with a reusable video flexible ureteroscope. Methods Patients undergoing retrograde flexible ureteroscopy at Nepean Hospital, Sydney, Australia, were included in this study. Three different flexible ureteroscopes were used in this study: (i) single‐use digital LithoVue (Boston Scientific, Marlborough, MA, USA); (ii) single‐use digital PU3022A (Pusen, Zhuhai, China); and (iii) reusable digital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 20 publications
0
58
0
Order By: Relevance
“…The case-control study performed by Usawachintachit et al found that the overall mean procedure time of single-use FURS was 10 min shorter than that of reusable FURS (19). Conversely, Kam et al found that single-use FURS was 10 min longer than that of the reusable FURS group (14). However, JK thought that the lower image quality associated with single-use FURS was responsible for this difference, although the operative duration is closely linked with the experience of the surgeon (14).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The case-control study performed by Usawachintachit et al found that the overall mean procedure time of single-use FURS was 10 min shorter than that of reusable FURS (19). Conversely, Kam et al found that single-use FURS was 10 min longer than that of the reusable FURS group (14). However, JK thought that the lower image quality associated with single-use FURS was responsible for this difference, although the operative duration is closely linked with the experience of the surgeon (14).…”
Section: Discussionmentioning
confidence: 99%
“…Four included studies provided enough data available on operative time (14,(18)(19)(20). In Kam's study, two different models of single-use FURS were compared with the same traditional FURS.…”
Section: Operative Timementioning
confidence: 99%
See 2 more Smart Citations
“…In this study, Kam et al . prospectively assessed both single‐use and reusable flexible ureteroscopes . Specifically, the single‐use LithoVue (Boston Scientific, Marlborough, MA, USA) and PU3022A (Pusen, Zhuhai, China) were compared with the reusable digital URF‐V2 (Olympus, Tokyo, Japan), utilizing a 5‐point Likert scale to subjectively assess visibility and maneuverability.…”
mentioning
confidence: 99%